The Effectiveness of Assertiveness Training on Resilience and Empathy in High School Girls in Varamin - Tajik Khaveh, Maryam; Andalib Koraim, Morteza; Zargami, Elham (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective:  The objective of this study was to determine the effectiveness of assertiveness training on enhancing resilience and empathy among high-school girls in Varamin.Methods and Materials: This quasi-experimental study employed a pre-test–post-test design with a control group. The statistical population included all high-school girls in Varamin, from which 30 participants were selected through convenient sampling. Participants were randomly assigned to experimental and control groups, each consisting of 15 students. The experimental group received assertiveness training across structured educational sessions, while the control group received no intervention during the study period. Data were collected using the Connor–Davidson Resilience Scale (CD-RISC) and the Davis Empathy Questionnaire, both of which demonstrated acceptable reliability in this study (α = 0.86 and α = 0.79, respectively). Descriptive statistics and inferential analyses, including multivariate and univariate analyses of covariance (MANCOVA and ANCOVA), were conducted using SPSS version 25 to compare post-test outcomes while controlling for pre-test scores.Findings: Inferential results showed a significant multivariate effect of group membership on the combined dependent variables of resilience and empathy (Pillai’s Trace = 0.930, F(2, 25) = 164.966, p < 0.001). Between-subject effects indicated that the intervention significantly improved resilience (F = 73.835, p < 0.001) and empathy (F = 232.690, p < 0.001) in the experimental group compared to the control group. Effect sizes were large for both variables (η² = 0.749 for resilience and η² = 0.899 for empathy), and statistical power values were high, demonstrating the robustness of the findings.Conclusion: The results indicate that assertiveness training is a highly effective intervention for improving both resilience and empathy among high-school girls. Incorporating assertiveness-based programs into school mental health initiatives may support adolescents’ emotional well-being and interpersonal functioning.